60. FACTORS ASSOCIATED WITH THE DURATION OF URETHRAL CATHETERIZATION FOLLOWING BENIGN PROSTATIC HYPERPLASIA USING BIPOLAR TRANSURETHRAL ENUCLEATION AT 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors associated with the duration of urethral catheterization following benign prostatic hyperplasia (BPH) using bipolar transurethral enucleation at 108 Military Central Hospital from 2024 to 2025.Methods: A prospective, longitudinal descriptive study was conducted on a case series of 68 patients with BPH who underwent bipolar transurethral enucleation.Results: The mean duration of catheterization was 2.3±1.4 days, with a median of 2 days (IQR 2-2). Analysis showed that factors significantly associated with the duration of catheterization included post-removal complications (p
Keywords: Benign prostatic hyperplasia; bipolar; transurethral enucleation; urethral catheterization.